Development of a Web-based Application to Enhance Salon Management for L Six Hair Studio - Lim, Ka Huat; Mat Nawi, Rosmamalmi (Applied Information Technology And Computer Science, 2023)
The L Six Hair Studio Management System is a web-based solution designed to streamline operations for employers, employees, and customers in the hairdressing business. This study aims to assess the effectiveness of the system in improving operational efficiency and customer experience. The research objectives include evaluating the system's impact on appointment management, inventory management, and overall operational efficiency. The study employs the waterfall methodology, following a sequential approach that involves requirements gathering, system design, implementation, testing, and deployment. Data for the study is collected through interviews with studio owners, employees, and customers, as well as system-generated data. Key findings indicate that the L Six Hair Studio Management System significantly enhances operational efficiency, streamlines appointment handling, and optimizes inventory management. The discussion highlights the importance of user-friendly interfaces and efficient functionalities and suggests future work to explore system customization and its long-term impact on the hairdressing business.